1999
DOI: 10.1002/(sici)1097-4628(19991031)74:5<1146::aid-app11>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Micro- and ultrafiltration film membranes from poly(ether ether ketone) (PEEK)

Abstract: Film membranes from the thermoplastic poly(ether ether ketone) (PEEK) have been extruded and tested for their microfiltration and ultrafiltration performance. High-performance asymmetric membranes have been obtained by extruding polymer blends of PEEK, polysulphone, and a small molecule solvent mixture, and then by removing the polysulphone and solvent in a subsequent extraction step. The process for making ultrafiltration membranes differs from microfiltration membranes only in the relative blend components, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Porous polymers, with their combination of low density, high surface area, and good insulation properties, have found many applications in the modern world for instance as insulation materials, [ 8 ] in composites [ 9 ] and as membranes. [ 10 ] Only a few examples of porous PEEK membranes and fibers [ 11,12 ] or foam monoliths [ 29 ] prepared by a temperature induced liquid–liquid phase separation or phase inversion process were reported. Most other examples of porous high performance polymer foams were produced by chemical or physical (gas) blowing [ 13,14 ] or particulate leaching.…”
Section: Figurementioning
confidence: 99%
“…Porous polymers, with their combination of low density, high surface area, and good insulation properties, have found many applications in the modern world for instance as insulation materials, [ 8 ] in composites [ 9 ] and as membranes. [ 10 ] Only a few examples of porous PEEK membranes and fibers [ 11,12 ] or foam monoliths [ 29 ] prepared by a temperature induced liquid–liquid phase separation or phase inversion process were reported. Most other examples of porous high performance polymer foams were produced by chemical or physical (gas) blowing [ 13,14 ] or particulate leaching.…”
Section: Figurementioning
confidence: 99%
“…It is well known that PEEK polymer is capable of providing numerous unique properties on temperature and solvent resistances. Except for the applications on the field of composites, PEEK can also be applied to the high‐performance of microfiltration membranes 3, 4. Nanoparticle‐filled PEEK composites have been successfully fabricated through the compression‐molding process 5–8.…”
Section: Introductionmentioning
confidence: 99%
“…Except for the applications on the field of composites, PEEK can also be applied to the high-performance of microfiltration membranes. 3,4 Nanoparticle-filled PEEK composites have been successfully fabricated through the compression-molding process. [5][6][7][8] It was reported that the alumina nanoparticles are scattered individually in the PEEK matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Using asymmetric membranes having surface pore sizes in the range of 1–50 nm, the ultrafiltration process separates extremely small, suspended particles and dissolved macromolecules from fluids 3. Because of its great importance, the study of the ultrafiltration process has become one of the top research areas in recent years 2–12. Numerous investigations have been focused on studies of the effects of operational conditions on the membrane performance, industrial applications, and fouling as well as the modeling of the transport properties of ultrafiltration 3, 4.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous investigations have been focused on studies of the effects of operational conditions on the membrane performance, industrial applications, and fouling as well as the modeling of the transport properties of ultrafiltration 3, 4. Some investigators have studied the preparation, morphology, and performance of inorganic and polymeric membranes 2, 3, 5–12. However, polymeric membranes are the most useful membranes used in various industries, especially in ultrafiltration, nanofiltration, reverse osmosis, and gas separation, because they can have various functional groups and be easily modified chemically 6.…”
Section: Introductionmentioning
confidence: 99%